The senior universities students in Portugal and Brazil - Jacob, Luis (2019)
Given the growth in the number of senior universities in Portugal and Brazil, we think it is important to know the audience which frequents these institutions, their motivations, the health impact and whether there are significant differences between the two countries. The authors have created a survey that was applied in person in Portugal and the State of Goiás in Brazil. With this study, it was possible to trace the profile of the students who attend the Senior Universities (US or U3A) in Portugal and universities open to Seniors (UNATI) in Brazil. We also added a study on volunteer teachers in the Portuguese US. We now know that are essentially women, aged 60-75 years and of all social and educational levels. As for the motives are essentially the conviviality, get active and learn. No significant differences were found between the two countries, in groups and in the motivations, with exception to the marital status and the number of courses attended